THE EFFECTIVENESS OF GRAMMAR TRANSLATION METHOD - Bakhromova Gulmira Ahmadjonovna (Journals Park Publishing, 2022)
The usefulness of the Grammar Translation approach in learning English was investigated by the researcher. This technique of instruction is employed in the study of foreign languages. People in Pakistan speak English as a second language. English is a required subject at educational institutions. It is taught in a variety of ways methods. The Grammar Translation Way is the most ancient method of language learning. As a result, in our country, it's a popular tool for learning foreign languages. The efficiency of this strategy is demonstrated in this publication. Quantitative analysis A questionnaire is used as a method to learn about the opinions of students on how much they value education. This strategy has made it easier for them to learn English.
Keywords: teaching methods; teching English; grammar translation